The Association Between Chronic Obstructive Pulmonary Disease and Depression and Other Mental Disorders: A Literature Review - Bednarek, Filip; Plinta, Olga; Hojda, Alicja; Nawrocka, Natalia; Rodak, Hanna; Małajewicz, Izabela; Pietrzyk, Małgorzata; Stępień, Dawid; Oskroba, Karolina (Quality in Sport, 2026)
Chronic obstructive pulmonary disease (COPD) already represents a growing global health challenge, whose implications and consequences extend beyond the respiratory system, encompassing various mental disorders, including depression, anxiety disorders, cognitive impairment, and sleep disturbances. This literature review, covering publications from recent years, analyzes the multifactorial mechanisms linking COPD with mental health disorders—beginning with chronic inflammation, hypoxia, oxidative stress, and increasing functional limitations. The presented data indicate that depression affects even more than one-third of COPD patients, intensifying somatic symptoms of the underlying disease, increasing the risk of exacerbations, hospitalizations, and mortality, and reducing treatment adherence and the effectiveness of rehabilitation. Similarly, anxiety disorders, cognitive impairment, and sleep disturbances, which often coexist with COPD, influence the perception of dyspnea, the ability to self-manage therapy, and overall patient functioning. This paper highlights the importance of early diagnosis of mental disorders using validated screening tools, as well as the need for a holistic model of care combining pharmacological interventions with non-pharmacological approaches based on pulmonary rehabilitation, cognitive-behavioral therapy, and psychosocial support. Integration of pulmonological and psychiatric perspectives is essential both for improving patients’ quality of life and optimizing prognosis. The findings point to an urgent need for further research on the mechanisms underlying comorbidities and the effectiveness of integrated treatment models.